PERTIMBANGAN PEMBERIAN PENGURANGAN PAJAK BPHTB PADA PANDEMI COVID-19 - Raja Mohamad Rozi; Nisya (Faculty of Law, Universitas Brawijaya, 2021)
Tax is an obligatory contribution of the people to the state which functions to finance all public interests, including finance development to aims for the welfare of the people. The current condition of the Covid 19 pandemic provides a responsive idea to provide taxpayers with “relief” as regulated in Governor Regulation Number 103 of 2011 concerning Granting of Deductions, Relief and Exemption of Duty on Acquiring Rights on Land and Buildings (BPHTB). Pro contra arise in relation to criteria issue for granting relief conflicting regulations with the legal concept of the phrase